High macroscopic neutron capture cross section ceramics based on bauxite and Gd2O3 - Hernández, Maria Florencia (2020)
The effect of the addition of Gadolinium oxide (Gd2O3) up to 10 wt.% in bauxite was studied and its thermal behavior compared with pure bauxite. The incorporation of Gd2O3 is of technological interest for the design of smart traceable ceramic proppants used for unconventional gas and oil well stimulation. These high macroscopic neutron capture cross section proppants are used to obtain relevant information, such as the location and height of the created hydraulic fractures, through a neutron based detection technology. The study comprised a set of thermal and sintering behavior analyses up to 1500 °C of mixtures up to 10 wt.% addition of Gd2O3. The developed texture and microstructure was also assessed. A simple mechanical characterization was performed as well. Fully-dense pore-free microstructures were developed, with alumina and mullite as the main crystalline phases. Gadolinium secondary and ternary alumino-silicate phases were also observed after thermal treatment. These present a needle morphology that might result in reinforcement mechanisms. No important glassy phase was detected; although sintering was enhanced, the Gd2O3 oxide main role was found to be as a sintering aid rather than a strict flux agent. The mechanical behavior remained fragile with the rare oxide addition. In fact, the mechanical resistance increased up to 20 wt.% for the 10 wt.% added sample. The oxide addition together with the bauxite dehydroxilation mass loss resulted in materials with up to 1.5 x 105 (c.u.) macroscopic neutron capture cross section materials. The obtained results permit to define design strategies of high macroscopic neutron capture ceramic materials for wellbore and developed fractures description.